Immunogenicity of recombinant TrxHA5.1M protein expressed in Pichia pastoris in chickens - Cuong, Vo Viet; Quy, Nguyen Thi; Ngoc, Nguyen Thanh; Thu Hong, Le Thi; Huyen, Do Thi; Dung, Truong Van; Hai, Truong Nam (Academia Journal of Biology, 2014)
Recombinant avian influenza vaccines offer several advantages over the conventional vaccines. In this study, the methylotropic yeast Pichia pastoris SMD1168 carrying a fusion gene TrxHA5.1m (coding for Trx and subunit HA1 of hemaglutinin antigen derived from highly pathogenic avian influenza H5N1) was used to produce TrxHA5.1M. The recombinant protein was suffered from glycosylation and protease processing. The TrxHA5.1M was partly purified by precipitation with 60% ammonium sulfate (mass/volumn) or purified using Co-NTA affinity chromatography. The doses of 100 μg TrxHA5.1M were immunized for two week-old chickens by subcutaneous injection or by intranasal administration for assessment of TrxHA5.1M immunogenicity. In subcutaneous injection chickens groups, haemagglutinin inhibition (HI) titer of chickens sera harvested after 2 weeks of booster immunization reached 7.0-7.2 log2. In intranasal immunization groups, HI titers were about 6.6-7.0 log2. There had no any significant difference in HI titers of sera from chickens immunized with partly purified or purified recombinant proteins.